Designing E-Book Based on TBL (Task Based Learning) for TEC (Totality English Course) - Afidah, Nurul; Putro, Tanagung Laksono; Hanifah, Hanifah; Maknun, Lukluil (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this research was to design an electronic book for Totality English Course that was called TEC BOOK. TEC BOOK was electronic book that was based on TBL for students in beginner level. The method of the research was Research and Development method. The researcher chose ADDIE to be the model of this research. ADDIE was model of research that consists of analysis, design, development, implementation, and evaluation in the steps. The approach of this study was quantitative and qualitative. Interview was used by the researcher to collect the data of need analysis, and questionnaire for collecting the data of implementation product. The subject of this research was the beginner students of Totality English Course (TEC). The result of need analysis showed that students needed a book to study in the course to make the study became more effective and interesting than before. The result of need analysis was supported by the result of implementation. The result showed that (90,76%) students of Totality English Course (TEC) were strongly agree about the implementation of TEC BOOK in TEC. The result of development showed that TEC BOOK got (82%) in validation of media and got (94%) in validation of material. It means that the media and material in TEC BOOK was valid. Based on that result TEC BOOK was ready to be used by the students of TEC in studying English.